Cross-Cultural Differences in the Use of Online Mental Health Support Forums - Pendse, Sachin R.; Niederhoffer, Kate; Sharma, Amit (ACM Conference on Computer-Supported Cooperative Work and Social Computing (CSCW), 2019)
Online mental health forums facilitate supportive relationships between peers that transcend national and cultural boundaries. While past work in medical anthropology indicates a central role of cultural identity in how individuals frame their mental well-being and distress, little research has been done to investigate the role of culture in seeking and providing mental health support on online forums. Using data from two mental health forums, we analyze cross-cultural differences in mental health expression between people from different countries. We characterize these differences along three dimensions–identity, language use, and support behavior. Through comparing usage of the platform by individuals from three Asian countries with their counterparts from primarily Western countries, we find that individuals from these less-represented countries mention their own country more often when expressing distress, use fewer clinical language terms, and are more likely to provide support to people from the same country as them, as expected from past work on mental health in these countries. Contrary to past work, however, we find that the use of clinical mental health language is not affected over time by interacting with others in an international forum. While these findings are useful for understanding the role of culture in mental health support, they also have practical design implications for online forums. We find that the three dimensions of cultural differences we analyze are correlated with receiving effective support, and make design recommendations that can improve quality of support for the people in the minority on these forums.